Women and Mentoring in Collegiate Athletics. Issue 5 (19th October 2016) - Smith, Allison B.; Taylor, Elizabeth A.; Hardin, Robin
Abstract : The number of women working and participating in intercollegiate athletics has steadily increased the past four decades. This has led for a need to develop women as leaders within collegiate athletics and one way of doing this is through mentoring. Mentoring provides guidance in regard to both the professional development and psychosocial support. In our research, we investigated mentoring within the college athletics environment by interviewing female athletic directors and female graduate assistants. Four themes emerged from the interviews: (a) importance of mentorship; (b) quality of mentorship; (c) availability, and (d) lack of female mentorship. Our research builds on the idea that mentorship is important and valued by both the mentor and protégé but the key is determining how to best connect the two groups. This would possibly lead to higher job satisfaction, higher employee retention, and more productive work environment.